Modified method of patency judgement using patency capsule prior to capsule endoscopy in clinical practice - Takahiro Miyazu; Satoshi Osawa; Satoshi Tamura; Shinya Tani; Natsuki Ishida; Tomoharu Matsuura; Mihoko Yamade; Moriya Iwaizumi; Yasushi Hamaya; Takahisa Furuta; Ken Sugimoto (Scientific Reports, 2022)
Abstract In 2012, Japan approved the use of a tag-less patency capsule (PC), which evaluates gastrointestinal patency before small-bowel capsule endoscopy (SBCE). This study aimed to evaluate the validity of our modification on the passage criteria for this PC in clinical practice. We retrospectively enrolled 326 consecutive patients who underwent PC examination before SBCE. If X-ray could not reveal the PC in the body during the judgement time (30–33 h after ingestion), we defined it as ‘estimated patency’ and performed SBCE. We employed plain computed tomography (CT) for the second judgement, as needed. The overall patency rate was 95.1%. By X-ray, 41 (12.6%) patients were judged to have ‘estimated patency’, and SBCE could be safely performed. Plain CT judgement was necessary in 106 patients (32.5%). One PC case had a residual coating film associated with stenosis in a patient with Crohn’s disease (CD), and one (0.3%) SBCE case had capsule retention resulting from false CT judgement. Multivariate analysis revealed that established CD and inpatient were factors related to no-patency. In conclusion, PC is useful for examining gastrointestinal patency, keeping in mind CT misjudgement. If PC was not found in the body via X-ray, performing SBCE as ‘estimated patency’ seemed appropriate.